Age differences in contemporary treatment of patients with chronic heart failure and reduced ejection fraction. (September 2019) - Veenis, Jesse F; Brunner-La Rocca, Hans-Peter; Linssen, Gerard CM; Geerlings, Peter R; Van Gent, Marco WF; Aksoy, Ismail; Oosterom, Liane; Moons, Arno HM; Hoes, Arno W; Brugts, Jasper J; ,
Background: Elderly patients are underrepresented in clinical trials but comprise the majority of heart failure patients. Data on age-specific use of heart failure therapy are limited. The European Society of Cardiology heart failure guidelines provide no age-specific treatment recommendations. We investigated practice-based heart failure management in a large registry at heart failure outpatient clinics. Design and methods: We studied 8351 heart failure with reduced ejection fraction patients at 34 Dutch outpatient clinics between 2013 and 2016. The mean age was 72.3 ± 11.8 years and we divided age into three categories: less than 60 years (13.9%); 60–74 years (36.0%); and 75 years and over (50.2%). Results: Elderly heart failure with reduced ejection fraction patients (≥75 years) received significantly fewer beta-blockers (77.8% vs. 84.2%), renin–angiotensin system inhibitors (75.2% vs. 89.7%), mineralocorticoid receptor antagonists (50.6% vs. 59.6%) and ivabradine (2.9% vs. 9.3%), but significantly more diuretics (88.1% vs. 72.6%) compared to patients aged less than 60 years ( P for all trends  < 0.01). Moreover, the prescribed target dosages were significantly lower in elderly patients. Also, implantable cardioverter defibrillator (18.9% vs. 44.1%) and cardiac resynchronisation therapy device (14.6% vs. 16.7%) implantation rates were significantly lower in elderly patients. A similar trend in drug prescription was observed in patients with heart failure with mid-range ejection fraction as in heart failure with reduced ejection fraction. Conclusion: With increasing age, heart failure with reduced ejection fraction patients less often received guideline-recommended medication prescriptions and also in a lower dosage. In addition, a lower percentage of implantable cardioverter defibrillator and cardiac resynchronisation therapy device implantation in elderly patients was observed.